Requirements for Establishing Smart School System in Algeria Based on Malaysian Smart School - Mahammed, Boukerraf (2010)
This project was proposed to identify the needed requirements for adoption of Smart School System in Algeria based on Malaysian Smart School. This study was conducted to seek the current weaknesses and the requirements. It proposes a feasible model to adopt this system. The methodology has been adapted from the method of Magliaro and Eziefe which consist of both qualitative and quantitative study. The results have been sought by questionnaire and literature review, which helped to identify the weaknesses and requirements to carry out this adoption in Algeria. The requirements have been achieved can motivate the Algerian government to launch an effective strategy, and to create a base on which future studies on the ICT integration into the Algerian educational system can be built. In addition the decision makers enable to apply this study for preparing the policy on using ICT to develop the educational sector in Algeria.